2022
DOI: 10.2196/34183
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Motivations for Alternative Cancer Therapy With Insights From a Crowdfunding Platform: Cross-sectional Mixed Methods Study

Abstract: Background Alternative cancer therapy is associated with increased mortality, but little is known about those who pursue it. Objective We aimed to describe individuals’ motivations for using alternative cancer therapies and determine whether motivations differ based on individuals’ timing of seeking alternative therapies. Methods We used data from 649 campaigns posted on the website GoFundMe between 2011 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…If the press transmits the message that alternative treatments are effective and offer more advantages than disadvantages, then a climate of opinion favourable to pseudoscience is fostered. This can potentially lead to the discontinuation of conventional therapies to replace them with alternative therapies without proven effectiveness, even for the treatment of serious diseases (Peterson et al, 2022). This scenario may become even more likely in the case of those readers whose clinical or therapeutic expectations have not been met to the degree they expected by conventional medicine .…”
Section: Lack Of An Editorial Perspective Regarding Pseudosciencementioning
confidence: 99%
See 1 more Smart Citation
“…If the press transmits the message that alternative treatments are effective and offer more advantages than disadvantages, then a climate of opinion favourable to pseudoscience is fostered. This can potentially lead to the discontinuation of conventional therapies to replace them with alternative therapies without proven effectiveness, even for the treatment of serious diseases (Peterson et al, 2022). This scenario may become even more likely in the case of those readers whose clinical or therapeutic expectations have not been met to the degree they expected by conventional medicine .…”
Section: Lack Of An Editorial Perspective Regarding Pseudosciencementioning
confidence: 99%
“…This misconception -to think that something, because it is natural, is capable of healing-has become a key decision driver for many people. Peterson et al (2022) described that patients who initially decided to treat cancer using alternative therapies were more likely to express values associated with a natural discourse.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Nevertheless, ACT use is frequent worldwide, and many individuals may turn to online crowdfunding sites, including GoFundMe® ( gofundme.com ), to help offset the often significant personal and family costs. 5 , 6 , 7 , 8 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“… 5 Other individuals opt to use ACT available in their home countries, including home remedies, mail order supplements, and in‐person treatments. Previous research has identified specific clinics that are common treatment destinations for the beneficiaries of online fundraisers seeking ACT abroad, 5 , 6 but the differences between campaigns for individuals who travel internationally for ACT and those that receive treatment in their home countries have not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation